Kinetics of two-pulsed photon echo formed on the 0–1 transition: isotropic and anisotropic collisions. (10th October 2018) - Gol'dort, V G; Ishchenko, V N; Khvorostov, E B; Kochubei, S A; Rubtsova, N N
Abstract: The photon echo formed at the intercombination (6s 2 ) 1 S0 (6s6p) 3 P1 (type 0–1) transition of ytterbium atoms 174 Yb by two pulses of resonance radiation was investigated as a function of the time delay between exciting pulses (the photon echo kinetics). For exciting radiation pulses of the same linear polarization in the delay region 70–250 ns, the photon echo kinetics is close to the exponential one both in pure ytterbium and in its mixtures with buffer gases Ar and Xe. The relaxation cross sections were determined for all three cases, taking into account the isotopic composition of xenon and ytterbium. For the first time, the complex nonmonotonous kinetics of the collision-induced photon echo was observed in the same mixtures for the forming pulses of linear mutually orthogonal polarization. The relative efficiency of buffer atoms Yb (other isotopes than 174 Yb), Xe and Ar in the collision-induced photon echo formation was obtained.